Encyklopedi om demenssjukdom - Karlberg, Ingvar (Socialmedicinsk tidskrift, 2016)
Titel: ”Om demens” Författare: Gunilla Armanius Björlin, Hans Basun, Barbro Beck-Friis, Sirkka-Lisa Ekman, Elisabet Englund, Maria Eriksdotter Jönhagen, Lars Gustafson, Lars Lannfelt, Louise Nygård, Karin Sparring Björkstén, Beata Terzis, Lars-Olof Wahlund och Anders Wimo. Förlag: Liber förlag 2004.